Analisi Yuridis Penerapan Asas Pemisahan Horisontal dan Pelekatan Vertikal Terhadap Peralihan Hak Atas Tanah Ditinjau dari Hukum Perdata - Evodius Eron Djerahu; Orpa J Nubatonis; Chatryen M Dju Bire (Law Faculty, Nusa Cendana University, 2026)
The transfer of land rights in Indonesia is regulated by various legal principles which sometimes conflict, especially between the principle of horizontal separation and the principle of vertical attachment. This research aims to analyze the application of these two principles in the context of Indonesian civil and land law. The method used is a normative legal approach by analyzing statutory regulatory documents, court decisions and expert views. The research results show that the principle of horizontal separation, which divides rights to land and objects attached to it, is regulated in the Civil Code and the Basic Agrarian Law (UUPA). Meanwhile, the principle of vertical attachment, which views land and attached objects as one unit, is reflected in the Civil Code and several related laws and regulations. The application of these principles in the transfer of rights affects how buildings, plants and other objects attached to land are legally regulated. The principle of horizontal separation allows the transfer of land rights without having to transfer rights to the objects attached, while the principle of vertical attachment causes these objects to automatically transfer rights. This research concludes that Indonesian land law tends to adhere to the principle of horizontal separation, as reflected in the UUPA, which provides clear regulations regarding the legal relationship between land and the objects on it.